Morphological peculiarates of gastritis in patients with chronic gastric erosions and biliary tract disease. - Solovyova, G. A.; Kurik, O. G. (Морфологія / Morphologia / Morfologìâ, 2012)
Article presents the morphological peculiarates of gastritis in patients with erosions with biliary tract disease in comparison with patients with gastric erosions and duodenal ulcer disease and chronic gastritis. It is revealed, that patients with gastric erosions and biliary tract diseases are characterized by bigger spreading of gastritis: inflammation, activity, atrophy, intestinal metaplasia with predominant small intestine in gastric body, intestine metaplasia in antral part of the stomach is revealed more frequently in these category of patients.